Nomophobia and Online Gambling Behavior in College Students - Debora, Disa Aulia; Wijaya, Hariz Enggar (Utan Kayu Publishing, 2025)
Much research has shown that online gambling behavior has detrimental effects on various aspects, including on undergraduate students. However, studies on smartphone behavior and online gambling among students are still under research. This study aims to determine the relationship between nomophobia and online gambling behavior among university students. A total sample of 118 undergraduate students who were using smartphones and actively playing online gambling participated in this study. We used the Nomophobia Questionnaire scale and the Online Gambling Symptom Assessment Scale to obtain nomophobia and online gambling behavior data. Correlation analysis showed a significant and positive correlation between nomophobia and online gambling behavior, with a coefficient r being 0.439 and a p-value being 0.000 (p<0.05). The results show that there is a positive relationship between nomophobia and online gambling behavior in college students. Gender analysis showed that there were no significant differences between male and female students in online gambling behavior, whereas in nomophobia, female students had higher levels than male students. These findings highlight the urgency of strengthening digital literacy to prevent online gambling behavior among undergraduate students.